Physical activity measurement in older adults: Wearables versus self-report - VandeBunte, Anna; Gontrum, Eva; Goldberger, Lauren; Fonseca, Corrina; Djukic, Nina; You, Michelle; Kramer, Joel H.; Casaletto, Kaitlin B. (Frontiers in Digital Health, 2022)
Physical activity (PA) is associated with preserved age-related brain health. However, PA quantification can vary. Actigraphy monitors are gold-standard but are less well validated in older adults, and when not feasible the Community Healthy Activities Model Program for Seniors (CHAMPS) and Physical Activity Scale for the Elderly (PASE) are widely accepted self-report questionnaires of PA. We aimed to compare these commonly used PA measures against one other, including their construct validity with a host of relevant outcomes. We also determine the factors that drive differences in PA reporting styles in older adults. 179 older adults completed 30-day Fitbit Flex2TM monitoring and reported PA levels via PASE and CHAMPS-METs (metabolic expenditure calories burned). Participants also completed measures of vascular (hypertension diagnosis, resting heart rate), neurobehavioral (cognition, Perceived Stress Scale, Everyday Cognition Scale), and brain MRI (medial temporal lobe volume) outcomes. Discrepancy between objective Fitbit monitoring and self-reported PA was evaluated using a sample-based z difference score. There were only modest relationships across all PA metrics. Fitbit step count demonstrated a stronger association with the PASE, whereas Fitbit calories was more strongly associated with CHAMPS-MET. Fitbit outcomes had more consistent convergence with relevant outcomes of interest (e.g., vascular and brain health indices) when compared to subjective measures; however, considerable heterogeneity within these associations was observed. A higher degree of overreporting was associated with worse memory and executive performances. We build on prior findings that wearable, objective indicators of PA demonstrate greater construct validity compared to self-report in older adults, and further show important clinical features (e.g., poorer cognitive status) of older adults that could contribute to a higher level of overreporting on self-report measures. Without specificity, it is difficult to pinpoint which aspects of PA contribute to brain health; characterization of what these measures truly operationalize help elucidate this relationship to provide more precise clinical recommendations for healthy aging.